ANALYSIS OF GRADE V STUDENTS' DIFFICULTIES IN SOLVING MATHEMATICS PROBLEMS BASED ON LOCAL CULTURE - Harahap, Syawal Fitrah; Hasibuan, Abrizal; Matondang, Akhirur Rhomadon; Saleh, Riswan; Simanjuntak, Susanti Maysura; Amir, Almira (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Mathematics learning that is disconnected from the cultural context of students often makes it difficult to understand concepts, especially at the elementary school level. Integration of local culture through an ethnomathematics approach is believed to be able to bridge this gap, but has not been widely studied from the perspective of students' cognitive and contextual difficulties. This study aims to identify and analyze the forms of difficulties faced by fifth grade students in solving mathematics problems based on the local Batak Angkola culture. This study uses a qualitative descriptive approach with 37 fifth grade students at SD Negeri 200117 Padangsidimpuan as subjects. Data collection techniques include observation, semi-structured interviews, and analysis of student work artifacts. Validation is carried out through triangulation of sources and time. Five main types of difficulties were found: understanding cultural context (27.03%), mathematical conceptual errors (21.62%), procedural errors (18.92%), calculation errors (16.22%), and not solving problems (16.22%). The conclusion of this study is that dominant difficulties arise due to the low connection between cultural representations in problems and students' mathematical understanding. A contextual learning strategy is needed that is designed with strengthening cultural literacy so that the integration of ethnomathematics becomes more effective.